From Headlines to Supply Lines: Paradoxes in the Digital News Media Supply Chain - Dubois, Derek; Ashraf, Muhammad Hasan; Yalçın, Mehmet Gökhan (Wiley, 2026)
Supply chain management has traditionally focused on networks of decision-making nodes that manage the physical flow of goods. In recent years, attention has increased to service supply chains. One underexplored example is that of news media, which has undergone a profound transformation due to digitalization. News media is considered both a unique service supply chain in its own right and an enabler of operant resources of knowledge for supply chain managers across many industries. Paradoxical tensions in this supply chain can inhibit knowledge creation and effective decision-making. As such, this study employs paradox theory to catalogue critical, persistent tensions arising from the digitalization of news media. Leveraging a systematic literature review, we contextualize these tensions and further propose both/and solutions that reconcile persistent competing demands. The findings advance the discipline by establishing the news media service supply chain as distinct and extending paradox theory into this new context. In practice, we recommend various strategies (e.g., integrating digital-native workflows, strengthening verification processes, improving media literacy, and embedding transparent governance mechanisms) to help reestablish credibility. Doing so ensures stakeholders can facilitate more effective knowledge management and mitigate many of the impacts that news media have on broader physical/service supply chains.
Keywords: Grand Challenges; Information Flow; News Media; Paradox Theory; Service Supply Chain